Intestinal Microbiota Regulate Certain Meat Quality Parameters in Chicken - Lei, Jiaqi; Dong, Yuanyang; Hou, Qihang; He, Yang; Lai, Yujiao; Liao, Chaoyong; Kawamura, Yoichiro; Li, Junyou; Zhang, Bingkun (Frontiers in Nutrition, 2022)
Growing evidence of intestinal microbiota-muscle axis provides a possibility to improve meat quality of broilers through regulating intestinal microbiota. Water-holding capacity is a crucial factor to evaluate the meat quality. High quality of water-holding capacity is usually described as a low drip-losing rate. This study aimed to explore the relationship between intestinal microbiota and water-holding capacity of muscle in broilers. According to our results, two native breeds of broilers (the Arbor Acres broilers and the Beijing-You broilers) exhibited remarkable differences in microbiota composition. However, the regular of gut bacteria compositions gradually became similar when the two breeds of broiler were raised in a same feeding environment. Therefore, this similar regular of intestinal microbiota induced similar water-holding capacity of the muscle from the two breeds. In subsequent fecal microbiota transplantation (FMT) experiments, the intestinal microbiota community of the Arbor Acres broilers was remodeling by oral gavage of bacterial suspension that was derived from the Beijing-You broilers. Then, not only body weight and abdominal fat rate were increased, but also drip loss of muscle was decreased in the Arbor Acres broilers. Additionally, muscle fiber diameter of biceps femoris muscle and expression of MyoD1 were notably enlarged. Muscle fiber diameter and related genes were deemed as important elements for water-holding capacity of muscle. Simultaneously, we screened typical intestinal bacteria in both the two native breeds of broilers by 16S rDNA sequencing. Lachnoclostridium was the only bacteria genus associated with drip-losing rate, meat fiber diameter, body weight, and abdominal fat rate. Importance Higher body weight and superior meat quality in livestock imply an adequate source of protein and substantial commercial value. Regulating the intestinal microbiota of broilers is a promising approach to optimize commercial phenotypes. Our results indicate that the intestinal microbiota profile could be reconstructed by external factors, leading to advantageous changes in muscle characteristics. The cecum microbiota of native broilers have the ability to improve certain meat quality and production performance. The population of Lachnoclostridium spp. could be used to regulate body weight and drip-losing rate in broilers, but more study is needed.